2016
DOI: 10.1111/jfd.12527
|View full text |Cite
|
Sign up to set email alerts
|

Positive correlation between Aeromonas salmonicida vaccine antigen concentration and protection in vaccinated rainbow trout Oncorhynchus mykiss evaluated by a tail fin infection model

Abstract: Rainbow trout, Oncorhynchus mykiss (Walbaum), are able to raise a protective immune response against Aeromonas salmonicida subsp. salmonicida (AS) following injection vaccination with commercial vaccines containing formalin-killed bacteria, but the protection is often suboptimal under Danish mariculture conditions. We elucidated whether protection can be improved by increasing the concentration of antigen (formalin-killed bacteria) in the vaccine. Rainbow trout juveniles were vaccinated by intraperitoneal (i.p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Antigens are presented to central lymphoid organs following uptake whereupon protective immune responses are initiated (Chilmonczyk, ; Tatner, ; Tatner & Manning, ; Zapata, Diez, Cejalvo, Gutierrez‐de Frias, & Cortes, ) and it may be hypothesized that this process may be less effective in immersion vaccinated fish. Thus, the antigen concentration in a vaccine is positively correlated with protection and antibody production of fish (Dubey et al., ; Marana et al., ), which will support the notion that immunization efficacy by immersion is lower than injection. This is supported by investigations showing that administration of vaccine by injection significantly improve survival rate and/or raised antibody levels compared to the immersion vaccinated and unvaccinated control groups (Chettri et al., , ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Antigens are presented to central lymphoid organs following uptake whereupon protective immune responses are initiated (Chilmonczyk, ; Tatner, ; Tatner & Manning, ; Zapata, Diez, Cejalvo, Gutierrez‐de Frias, & Cortes, ) and it may be hypothesized that this process may be less effective in immersion vaccinated fish. Thus, the antigen concentration in a vaccine is positively correlated with protection and antibody production of fish (Dubey et al., ; Marana et al., ), which will support the notion that immunization efficacy by immersion is lower than injection. This is supported by investigations showing that administration of vaccine by injection significantly improve survival rate and/or raised antibody levels compared to the immersion vaccinated and unvaccinated control groups (Chettri et al., , ).…”
Section: Discussionmentioning
confidence: 77%
“…Sublethal exposure of vaccinated fish to live bacteria was performed using a Danish strain of Y. ruckeri O1 biotype 2 (100415‐1/4), which originally was obtained from an ERM outbreak in a Danish trout farm (Dalsgaard & Madsen, ; Wheeler et al., ). Fish were anesthetized with MS222, and the upper part of the caudal fin was punctured using an epidermal puncture device for fish fins (Marana et al., ), which produced 10 perforations of the tail fin epidermis to allow bacterial entry. The live bacteria were administered by adding 100 μl of bacterin (7.7 × 10 8 CFU) on the punctured fin for 90 s. After exposure to the live bacteria, fish were placed in a small aerated fish tank for recovery whereafter the exposed fish were returned to the experimental tanks (water volume 100 L).…”
Section: Methodsmentioning
confidence: 99%
“…injection. The vaccine efficacy was assessed by infection trial and by measuring the antibody reactivity in immunized fish on grounds that the antibody response has in several studies confirmed to be closely correlated to protection [ 14 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have developed and tested a new challenge method that aims to mimic the natural infection route in aquaculture settings [11]. This method takes into consideration that fish in aquaculture are prone to physical injuries due to fin biting [12] [13] [14].…”
Section: Immunoprophylactic Measures With Focus On Vaccination Represmentioning
confidence: 99%
“…At 17 weeks post-vaccination (wpv) 50 vaccinated fish and 50 control fish in duplicate tanks (each containing 25 fish, now with a mean weight of 45 g) were challenged with AS by a new challenge method using a multi-puncture device [11]. The multi-puncture device was composed of a plastic cylinder equipped with a rubber plug carrying 10 steel needles ( Figure 1).…”
Section: Challengementioning
confidence: 99%